Insulator foci distance correlates with cellular and nuclear morphology in early Drosophila embryos. - Li, M.; Zhao, Q.; Belloli, R.; Duffy, C.R.; Cai, H.N. (Developmental Biology, 2021)
The three-dimensional (3D) organization of the genome is highly dynamic, changing during development and varying across different tissues and cell types. Recent studies indicate that these changes alter regulatory interactions, leading to changes in gene expression. Despite its importance, the mechanisms that influence genomic organization remain poorly understood. We have previously identified a network of chromatin boundary elements, or insulators, in the Drosophila Antennapedia homeotic complex (ANT-C). These genomic elements interact with one another to tether chromatin loops that could block or promote enhancer-promoter interactions. To understand the function of these insulators, we assessed their interactions by measuring their 3D nuclear distance in developing animal tissues. Our data suggest that the ANT-C Hox complex might be in a folded or looped configuration rather than in a random or extended form. The architecture of the ANT-C complex, as read out by the pair-wise distance between insulators, undergoes a strong compression during late embryogenesis, coinciding with the reduction of cell and nuclear diameters due to continued cell divisions in post-cleavage cells. Our results suggest that genomic architecture and gene regulation may be influenced by cellular morphology and movement during development.